2022
DOI: 10.1007/s10657-022-09754-5
|View full text |Cite
|
Sign up to set email alerts
|

Net neutrality and high-speed broadband networks: evidence from OECD countries

Abstract: Network neutrality regulations are intended to preserve the Internet as a non-discriminatory, public network and an open platform for innovation. Whereas the U.S. reversed its regulations in 2017, returning to a less strict regime, the EU has maintained its course and recently revised implementation guidelines for its strict and rather interventionist net neutrality regulations. To this day, there exist only a few empirical investigations on the impact of network neutrality regulations, based on rather broad m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It is suggested that NN regulation costs the UK as much as £340 million each year in lost network investment (Barclays Bank PLC, 2022), to say nothing of consumers and innovators who don't get to enjoy and deploy advanced services. The definitive study of fibre‐to‐the‐home investment on a panel of 32 OECD countries over 20 years shows that NN regulation has had a negative impact on network investment (Briglauer et al, 2022).…”
Section: How Net Neutrality Regulation Harms Consumersmentioning
confidence: 99%
“…It is suggested that NN regulation costs the UK as much as £340 million each year in lost network investment (Barclays Bank PLC, 2022), to say nothing of consumers and innovators who don't get to enjoy and deploy advanced services. The definitive study of fibre‐to‐the‐home investment on a panel of 32 OECD countries over 20 years shows that NN regulation has had a negative impact on network investment (Briglauer et al, 2022).…”
Section: How Net Neutrality Regulation Harms Consumersmentioning
confidence: 99%